Multi-Cultural Expedition into Mindfulness among High School Students - Owen, Jonathan; Kalavala, Prathyusha (Journal of International Students, 2012)
Many international college students know first-hand that striving for academic success can be stressful, especially far apart from the support and comfort of home. In today’s fast paced world, hardly anyone is exempt from stress, and American high school students are no exception. A recent University of California at Los Angeles study discovered that, among 106 secondary school students, the percentage reporting good or above-average high school emotional well-being declined from 55.3 percent in 2009 to 51.9 percent in 2010 (Nauert, 2011). In an attempt to curb this trend, during the fall semester of 2011, a local high school psychology teacher invited the authors of this article to speak with her 4 psychology classes about stress and relaxation as part of a continuing collaboration with Arkansas State University professors of psychology.